2011
DOI: 10.1038/ijo.2011.59
|View full text |Cite
|
Sign up to set email alerts
|

Dietary glycemic index and glycemic load in relation to risk of overweight in Japanese children and adolescents: the Ryukyus Child Health Study

Abstract: Objective: Epidemiologic evidence concerning the role of dietary glycemic index (GI) and glycemic load (GL) in obesity during childhood and adolescence is limited, particularly in non-Western populations. We examined the association between dietary GI and GL as well as dietary fiber intake and overweight status in Japanese children and adolescents. Subjects: This Japanese cross-sectional study included 15 974 children (6-11 years; 7956 boys and 8018 girls) and 8202 adolescents (12-15 years; 3944 boys and 4258 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 47 publications
3
38
2
Order By: Relevance
“…The mechanism linking a higher rate of eating and overweight has been speculated to involve increasing energy intake; hence, we did not adjust for energy intake in our analysis. In the present study, underreporting of energy intake, assessed based on the ratio of reported energy intake to estimated energy requirement, was prevalent, particularly in overweight subjects (15). Nonetheless, a higher rate of eating was associated with not only an increased risk of overweight but also a higher energy intake.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The mechanism linking a higher rate of eating and overweight has been speculated to involve increasing energy intake; hence, we did not adjust for energy intake in our analysis. In the present study, underreporting of energy intake, assessed based on the ratio of reported energy intake to estimated energy requirement, was prevalent, particularly in overweight subjects (15). Nonetheless, a higher rate of eating was associated with not only an increased risk of overweight but also a higher energy intake.…”
Section: Discussionmentioning
confidence: 78%
“…Of the 38,212 eligible students, 28,885 (75.6% of the eligible sample) participated in RYUCHS. Excluded from the present analysis were 3,581 students with incomplete data on the variables under study, and 1,128 who reported extremely low or high energy intake (Ͻ625-1,225 or Ͼ2,475-4,650 kcal/d, depending on age and sex) (15,16). The fi nal sample thus consisted of 24,176 students (63.3% of the eligible sample).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We excluded 16 subjects who reported extremely low or high energy intake (i.e., ,0.5 times the estimated energy requirement value for the lowest physical activity category or .1.5 times that for the highest physical activity category, according to the dietary reference intakes for Japanese issued in 2015). The exclusion criteria used in the study of Murakami et al (8) were applied in the present study.…”
Section: Methodsmentioning
confidence: 99%